Analisis Problematika Pembelajaran Matematika dan Solusi Alternatif di SMP Negeri 1 Rambang - Nastri Meliyani (Jurnal Educatio FKIP UNMA, 2021)
This study aims to describe the problems in learning mathematics and their alternative solutions at Rambang 1 State Junior High School. The method used in this research is a qualitative approach. The research subjects were two students from class IX-1 and class IX-6 and two mathematics teachers at SMP Negeri 1 Rambang who taught in grades IX-1 and IX-6. The research instruments used in this study were observation, questionnaires and interviews. The results of this study indicate the problems of learning mathematics in SMP Negeri 1 Rambang, namely mastery of mathematical concepts that are not good and motivation to learn is not good. Alternative solutions to these problems are scaffolding, a personal approach to students, the use of learning media that is more attractive to students' motivation in learning mathematics, and the application of learning methods that are in accordance with the characteristics of students. Keywords: Problems, Learning, Mathematics, Solutions.